2018
DOI: 10.1002/er.4118
|View full text |Cite
|
Sign up to set email alerts
|

Photon energy amplification for the design of a micro PV panel

Abstract: Summary To design a micro PV panel, thousands of photons have been produced from a single photon by breaking down its photonic structure using Higgs‐Boson BR (H → γγ¯) quantum field under high temperature conditions. Because the Higgs‐Boson BR (H → γγ¯) Quantum can be excited under high temperature conditions which forms extremely short‐range week force by the photon‐photon collusion of the bare ions; thus, a pair photon (e+e−) is created from a single photon. This pair of photon can be dissociated by 2 surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 48 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…The current flow into the circuit cells which is determined by the functional mode of its P-N junction that is able to produce electricity by conducting the interconnection of series-parallel configuration of the circuit cell (34,47,52). Implementation of the standard single diode circuit cell, the function of Ns series and Np parallel connection in relation to current generation can be expressed as…”
Section: Bio Energymentioning
confidence: 99%
“…The current flow into the circuit cells which is determined by the functional mode of its P-N junction that is able to produce electricity by conducting the interconnection of series-parallel configuration of the circuit cell (34,47,52). Implementation of the standard single diode circuit cell, the function of Ns series and Np parallel connection in relation to current generation can be expressed as…”
Section: Bio Energymentioning
confidence: 99%
“…Although several excellent works on perovskite solar cells (PSC) developed into a promising branch of renewable energy conversion have been conducted to increase up to 22.1% efficiency during the last several years, stabilizing them under the operating condition without compromising optimal optoelectronic properties remains challenging, and thus, this achievement is not satisfactory enough to trap solar energy massively for commercial use throughout the world (21,21). Thus, it has presented an unsurmountable challenge to date for commercial used solar energy globally with an attractive efficiency rate (4,19). Interestingly, recent studies revealed that pair-photon formation from a single one is doable via photon-photon collision of a single photon once implemented by high thermal conditions but difficult to demonstrate the potential applications of this energy commercially (1,5,9).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has presented an unsurmountable challenge to date for commercial used solar energy globally with an attractive e ciency rate (4,19). Interestingly, recent studies revealed that pair-photon formation from a single one is doable via photon-photon collision of a single photon once implemented by high thermal conditions but di cult to demonstrate the potential applications of this energy commercially (1,5,9).…”
Section: Introductionmentioning
confidence: 99%